AKTIVITAS MEDIA RELATIONS KABUPATEN BENGKALIS DALAM MEMPERTAHANKAN CITRA POSITIF - Atina, Liza; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Bengkalis regency is one of the government agencies that run the activities of publc relations. In every government agency, of course, have a good problem. Bengkalis district also experienced it. Along with the development of the media has become one of the tools to help disseminate information or news related to organization or government agencies. Public ralations Bengkalis district utilize media relations in maintaining a positive image.The research uses descriptive qualitative research type whit data collection method of interview, observation and documentation. To determine the subject, the research is interactive analsis model. To test the validity of the researcher uses extension of patricipation and data trisngulstion.The results of this study indicate that the public relations Bengkalis make massmedia as partners in in order to obtain a balanced publicity, forming a positive image and harmonious relationship with the mass media. Media relations activiover the spread of press releases, pers confies of bengkalis public relation bureau crences, perss visite, pers receptions, personal information service (news service) and anticipate contingency plan. Positive image of Bengkalis regency government in the eyes of the media well in line with the cooperation. Nevetheless, there are still public who think badly to the government of Bengkalis regency. Humas consider it all a challenge for them to stay afloat in an effort to maintain a positive image.Keywords: Public Relations, Media Relations, Image